Susceptibility to reinfection with SARS-CoV-2 virus relative to existing antibody concentrations and T cell response. (June 2023) - Atef, Shereen; Al Hosani, Farida; AbdelWareth, Laila; Al-Rifai, Rami H.; Abuyadek, Rowan; Jabari, Andrea; Ali, Raghib; Altrabulsi, Basel; Dunachie, Susanna; Alatoom, Adnan; Donnelly, James G
Highlights: Living conditions affect the exposure to SARS-CoV-2 in vaccinated individuals. T cell reactivity to SARS-CoV-2 wanes over time. Reinfection of dormitory dwellers occurred as Omicron spread. T cell reactivity greatly increased the protection from reinfection to SARS-CoV-2. Elevated SARS-CoV-2 titers did not confer complete immunity. Abstract: Objectives: We investigated the reinfection rate of vaccinated or convalescent immunized SARS-CoV-2 in 952 expatriate workers with SARS-CoV-2 serological antibody (Ab) patterns and surrogate T cell memory at recruitment and follow-up. Methods: Trimeric spike, nucleocapsid, and neutralizing Abs were measured, along with a T cell stimulation assay, targeting SARS-CoV-2 memory in clusters of differentiation (CD) 4+ and CD8+ T cells. The subjects were then followed up for reinfection for up to 6 months. Results: The seroprevalence positivity at enrollment was greater than 99%. The T cell reactivity in this population was 38.2%. Of the 149 (15.9%) participants that were reinfected during the follow-up period (74.3%) had nonreactive T cells at enrollment. Those who had greater than 100 binding Ab units/ml increase from the median concentration of antispike immunoglobulin G Abs had a 6% reduction in the risk of infection. Those who were below the median concentration had a 78% greater risk of infection. Conclusion: Significant immune protection from reinfection was observed in those who retained T cell activation memory. Additional protection was observed when the antispike was greater than the median value.